1997
DOI: 10.1021/bi970417q
|View full text |Cite
|
Sign up to set email alerts
|

The Dihydropyridine Dexniguldipine Hydrochloride Inhibits Cleavage and Religation Reactions of Eukaryotic DNA Topoisomerase I

Abstract: Dexniguldipine hydrochloride (B859-35, a dihydropyridine with antitumor and multidrug resistance-reverting activity) inhibits both the DNA cleavage and religation reactions of purified human DNA topoisomerase I at concentrations >1 microM, whereas at concentrations <1 microM it inhibits selectively the religation step and stabilizes the covalent topoisomerase I-DNA intermediate in a similar fashion as camptothecin. Inhibition of religation by camptothecin can be overcome by increasing the concentration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…We show here that camptothecin further attenuates the slow fraction of nucleoplasmic topoisomerase I, which supports the above notion of this fraction being the one engaged in DNA turnover. At least in living cells, the drug does not immobilize topoisomerase I completely, which fits some previous biochemical data (19) showing that topoisomerase I⅐DNA intermediates stabilized by camptothecin have a comparatively short half-life (Ͻ1 min). Why does topoisomerase I disappear so rapidly from its favored nucleolar residence when camptothecin is present?…”
Section: Localization and Mobility Of Gfp-topoisomerase I In Living Csupporting
confidence: 89%
“…We show here that camptothecin further attenuates the slow fraction of nucleoplasmic topoisomerase I, which supports the above notion of this fraction being the one engaged in DNA turnover. At least in living cells, the drug does not immobilize topoisomerase I completely, which fits some previous biochemical data (19) showing that topoisomerase I⅐DNA intermediates stabilized by camptothecin have a comparatively short half-life (Ͻ1 min). Why does topoisomerase I disappear so rapidly from its favored nucleolar residence when camptothecin is present?…”
Section: Localization and Mobility Of Gfp-topoisomerase I In Living Csupporting
confidence: 89%
“…We therefore believe that the sites of occupancy of the drugs and the incoming nucleophile (tyramine or the 5Ј-OH DNA end) are the same, partially overlapping or at least in close enough proximity to elicit mutual competition. Such a drug interaction mode with Flp is consistent with previously published results demonstrating that CPT inhibits topo I-mediated ligation in a competitive manner (31). Moreover, the similarity in the inhibition of Flp-mediated cleavage and ligation suggests that the two reactions are catalyzed by similar active site conformations.…”
Section: Cpt and Nsc-314622 Inhibit Flp Transesterification In A Compsupporting
confidence: 91%
“…The specific role of the bioactivity of pyridine ring has been recognized and the introduction of some pyridine analogs into the molecules of drugs could result in new compounds that have significant biological activity compared with the parent compounds Straub et al, 1997;Bolognese et al, 2002;Tiwari et al, 2002;Kuo et al, 2005). It was also reported that a diverse array of naturally occurring alkaloids in sponges exhibit potent bioactivities because of the presence of a pyridine moiety (Vincent et al, 1997;Gordon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%